"Living and building in Marine Resexes in the Amazon” - the functional and symbolic dimensions of the houses of traditional populations (PerCursos, 2024)
This article analyzes the dissonances between the functional and symbolic dimensions, which materialize in houses’ construction in a Marine Resex, and the socio-territorial and cultural needs of the traditional populations that inhabit the houses built with resources from the Housing Credit of the II National Agrarian Reform Program (II PNRA), in the Caeté-Taperaçu Marine Extractive Reserve, Bragança-PA. The qualitative methodology is used in nature and is based on semi-structured interviews and socioeconomic questionnaires applied to Resex residents, in the analysis of records, documents and data from official websites. From the sociological and interdisciplinary field, conflicts and the redefinition of the ways of living and building houses of traditional local populations are analyzed. In one hand, there is public policy which, following the building standard established by the State, aims to popularize and make housing construction cheaper for the poor (Valladares; Figueiredo, 1981), producing homogenization; on the other hand, it is observed the agency of families who produce other symbols through the act of inhabiting and (re)building their homes. These people, even at a disadvantage in the possession of capital – economic, political, social (Bourdieu, 1998) – produce other meanings for “green houses”, as the constructions originating from the II PNRA are called. The results show that “the doing resulting from inhabiting” (Sennett, 2018) reveals how the functional changes of housing add sociocultural elements of its cultural traditions to its symbolic dimension. Still, linked to the way of life of the traditional populations of this region, the effects of housing policy point to the lack of uniqueness of housing for the purposes of the traditional coastal-marine extractive population, and the absence of a view regarding environmental conservation for the who live in this Amazon region. The conquest of traditional populations to the right to housing comes up against the lack of universal access and the fragility of buildings that do not comply with their ways of life, their needs that are related to the rivers, mangroves and the sea.
Keywords: extractive reserves; housing policy; inhabiting; Amazon; house-home